Water Management in Sustainable Tourism: A Bibliometric - Loso Judijanto; Rini Fitrianingrum (West Science Social and Humanities Studies, 2026)
The current study seeks to examine the intellectual structure and evolution of water management as a part of the sustainable tourism research domain via bibliometric analysis approach. Based on publication data obtained from the scientific database and further analyzed using VOSviewer software, the study analyzes patterns of co-authorship, keywords' co-occurrences, thematic clustering, and citation performance in order to determine major trends and knowledge structure within the research domain. As the results show, sustainable development is identified as the main conceptual core of the domain, which tightly connects tourism, environmental sustainability, and water management. Key thematic clusters cover water resources management, ecotourism and ecosystem services, environmental degradation and pollution, as well as geoinformatics techniques like GIS and remote sensing. It was also discovered that over time there has been a shift from publications on environmental impacts and pollution towards more recent studies focused on water governance, adaptation to climate change and sustainable technological solutions. As for the pattern of cooperation, the field can be described as internationally connected but at the same time imbalanced, with several countries and organizations dominating in knowledge production.